Note
C03-0012-001 Bill Posting - £7.10/- Printing Publicity Circulation Tickets - sold before - on (circulars) - sold at door (Admission) Collection - who to do collection - actual collection & checking. Stewards Literature Order outside Programme 292C/946/3/12